2016
DOI: 10.1177/2048872616675485
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous balloon atrial septostomy on top of venoarterial extracorporeal membrane oxygenation results in safe and effective left heart decompression

Abstract: Percutaneous BAS may be a safe and efficient strategy for discharging the LA in both adults and children supported by VA-ECMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 39 publications
1
48
0
1
Order By: Relevance
“…8,12 Percutaneous balloon atrial septostomy may be a safe and efficient strategy for discharging the left atrium in both adults and children supported by VA-ECMO. 16 One adult patient in the preoperative group had left ventricular distention during extracorporeal support. This complication was treated by balloon atrial septostomy at the coronary angiography unit.…”
Section: Ender Gedik Et Al/experimental and Clinical Transplantation mentioning
confidence: 99%
“…8,12 Percutaneous balloon atrial septostomy may be a safe and efficient strategy for discharging the left atrium in both adults and children supported by VA-ECMO. 16 One adult patient in the preoperative group had left ventricular distention during extracorporeal support. This complication was treated by balloon atrial septostomy at the coronary angiography unit.…”
Section: Ender Gedik Et Al/experimental and Clinical Transplantation mentioning
confidence: 99%
“…In another single-center case series (37 pediatric patients), trans-catheter procedures to decompress the left heart were performed in 97% of patients within 24 h of ECMO initiation [4]. In a multi-center case series (64 patients: 32 adult, 32 pediatric) and the only study to include adult patients with available data on timing of intervention, Baruteau et al [5] report that the mean ECMO-BAS timing was 1.5 days, with a range of 0 to 12 days. In a literature summary by the same authors, previously reported mean ECMO-BAS timings for pediatric patients ranged from 8 h to 2.5 days.…”
mentioning
confidence: 99%
“…Interventional approaches to decompress the left heart include cardiac support interventions, such as intra-aortic balloon pumps, and percutaneous techniques to vent the left heart, such as pulmonary artery vents, retrograde transaortic vents, transseptal LA decompression [6, 9] with BAS and LA vent insertion [9], static over-the-wire [5, 9] balloon dilation, blade balloon septostomy [7, 9] and atrial stenting [9, 10]. The combination of BAS with ECMO has been shown to be safe and efficient in 64 patients in a multi-institutional study [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several techniques have been described in order to decompress the failing left heart, including intraaortic balloon pumps (IABPs), axial flow catheters (Impella, Abiomed Inc., Danvers, MA, USA) and left atrial to femoral artery bypass (TandemHeart, Cardiac Assist Inc., Pittsburgh, PA, USA) (10,11). Left heart decompression has also been achieved by the transcatheter creation of an atrial septal defect using different approaches, including vent placement, static balloon dilation and stent implantation (12)(13)(14).…”
mentioning
confidence: 99%